2013
DOI: 10.1021/es401722j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical and Physical Properties of Activated Carbon Powders on Oxygen Reduction and Microbial Fuel Cell Performance

Abstract: Commercially available activated carbon (AC) powders made from different precursor materials (coal, peat, coconut shell, hardwood, and phenolic resin) were electrochemically evaluated as oxygen reduction catalysts and tested as cathode catalysts in microbial fuel cells (MFCs). AC powders were characterized in terms of surface chemistry and porosity, and their kinetic activities were compared to carbon black and platinum catalysts in rotating disk electrode (RDE) tests. Cathodes using the coal-derived AC had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 35 publications
(81 reference statements)
4
130
2
1
Order By: Relevance
“…In fact, it has been shown that i) surface chemistry, 22 ii) temperature treatment, 19,25 iii) pressure applied, 19 iv) AC loading, 22 v) content of binder (e.g. PTFE), 22 vi) addition of carbon black, 26 affect the cathode performances and the MFC output significantly. AC seems to be the cheapest and efficient solution to adopt for scaling up MFCs.…”
mentioning
confidence: 99%
“…In fact, it has been shown that i) surface chemistry, 22 ii) temperature treatment, 19,25 iii) pressure applied, 19 iv) AC loading, 22 v) content of binder (e.g. PTFE), 22 vi) addition of carbon black, 26 affect the cathode performances and the MFC output significantly. AC seems to be the cheapest and efficient solution to adopt for scaling up MFCs.…”
mentioning
confidence: 99%
“…The fact that with the utilization of half of the reactant (oxygen) amount double amount of electrons is transferred, a 4-electrons transfer pathway is targeted in all researches [56].…”
Section: Oxygen Reduction Reaction Kinetics On Mfc Cathodementioning
confidence: 99%
“…An especially interesting catalyst is activated carbon, which is low cost and has a high catalytic activity. However, the mechanism how the activated carbon catalyzes oxygen reduction remains unclear (Watson et al, 2013). Another difficulty in reducing the cost of cathodes is the requirement of a complex gas-liquid-solid threephase interface for oxygen reduction, which makes the selection of cathode material and design of cathode structure more challenging.…”
Section: Reducing Capital Costmentioning
confidence: 99%